Biogeographic distribution and environmental drivers of tetracycline resistance genes in urban green spaces - Xunqiang Mo; Lingyue Lv; Jianzhong Xu; Zirui Meng; Xin Wen; Yu Liu; Runqiu Feng; Kai He; Jie Liu; Mengxuan He (Environmental and Sustainability Indicators)
Urban green spaces provide critical ecological and social benefits, acting as natural refuges that enhance the health and well-being of urban populations. However, anthropogenic practices—such as the use of reclaimed water for irrigation, manure-based fertilization, and atmospheric deposition—have contributed to the accumulation of tetracycline resistance genes (tet ARGs) in urban soils, posing emerging public health and environmental risks. Despite growing concern, the spatial distribution patterns and environmental drivers of tet ARGs in urban green spaces remain poorly understood. In this study, we compared the performance of multiple linear regression (MLR), geographically weighted regression (GWR), and multi-scale geographically weighted regression (MGWR) models in predicting the spatial distribution of tet ARGs across urban green spaces in Tianjin, China, using eight environmental and anthropogenic variables. The MGWR model demonstrated superior predictive accuracy, yielding improvements in adjusted R2 by 0.22 and 0.02 over the MLR and GWR models, respectively. Spatial analyses revealed a pronounced northward increase in tet ARG abundance, with concentrations primarily localized in the northern and eastern districts of the city. Key predictors included proximity to aquaculture farms, hospitals, livestock farms, pharmaceutical facilities, waste transfer stations, and the normalized difference vegetation index (NDVI). Our findings underscore the value of spatially explicit modeling in identifying hotspots and drivers of antibiotic resistance in urban ecosystems. This work provides essential insights for the targeted management of ARGs in green infrastructure, contributing to the broader goals of public health protection and sustainable urban environmental governance.